Long shadows : truth, lies and history - Paris, Erna, 1938-2022. (London : Bloomsbury, 2001)
Journeys around the world to investigate areas still reeling from past conflicts, from the United States and its memory of slavery to Japan, France, and Germany, where the unrelenting pain of Hiroshima and the Holocaust still exists.
Memory and the Second World War -- War, memory and race -- War, memory and identity -- Is there justice?
Originally published: Toronto : Knopf Canada, 2000.
Keywords: 1900-1999; History, Modern -- 20th century -- Historiography; Ethnicity; ethnicity; Ethnicity; History, Modern -- Historiography